Solid-state and flexible black electrochromic devices enabled by Ni-Cu salts based organohydrogel electrolytes - Guo, Xiaoyu (2023)
Solid-state black electrochromic devices (ECDs) are promising for smart window applications, particularly when privacy protection and low leakage are required. Herein, a Ni–Cu salts/poly(vinyl alcohol) based organohydrogel electrolyte is developed with superior visible-light transparency (83.8%), ionic conductivity (0.11 mS cm−1), and mechanical properties (tensile strength: 11.1 kPa, breaking strain: 242.6%). Due to the high viscosity of the organohydrogel electrolyte, a homogeneous Ni–Cu alloy film with a surface roughness of around 11.2 nm can be electrodeposited under −3 V for 5 min, and the resulting black color can be retained for over 350 min with a transmittance increase of only 5% at the voltage-off state. The solid-state rigid ECD exhibits an outstanding optical contrast between the transparent and colored states (visible light transmittance: 70.8% vs 0.085%), excellent cycling stability with over 90% retention of optical contrast after 2000 cycles. Finally, a flexible ECD is fabricated with the organohydrogel electrolyte and annealed indium tin oxide (ITO)-coated polyethylene naphthalate (PEN) films as flexible and durable electrodes. It exhibits good mechanical flexibility with transmittance modulation degradation of 10% after 800 bending cycles and switching stability for 400 cycles with up to 43% optical contrast.